Prediction of Sensory Crispness of Potato Chips Using a Reference-Calibration Method - Han Sub Kwak; Sang Sook Kim; Yoon Hyuk Chang; Mohammed Saleh; Youngseung Lee (Journal of Food Quality, 2019)
Reference calibration is a useful technique when sensory evaluation is not feasible or practical. This study was conducted to predict the crispness perception of potato chips evaluated by instrumental means through the reference-calibrated method. To investigate the relationship between sensory evaluation and instrumental measurement data, six different standard references for crispness were used. Instrumental crispness was predicted by measuring the total area of the chip with a texture analyzer. The samples were also evaluated by six trained panelists. Nine chips with various textures were tested by a mechanical test. The Fechner, Stevens, and Beidler models were applied to investigate the correlation across the reference scores with the total area then predicting the sensory crispness for the nine chips. The relationship between the instrumental total area and the sensory crispness of the standard references was found to be nonlinear over the standard crispness scale. The Fechner model seemed to be the best predictive model (R2 = 0.8; RMSEC = 1.3; robustness = 2.4; model discrimination index = 3.3) for predicting the sensory crispness of chips. This study suggests that standard references with a reference-calibration method can be used to calibrate the crispness of potato chips. It is the first study to demonstrate that sensory crispness of potato chips could be predicted using comprehensive references for crispness. Based on the results in this study, an equation established by the Fechner model could be utilized to estimate the various crispness of potato chips under circumstances in which sensory evaluation is not practical or available.